Alternative Sources of Financing University Education in Lagos State, Nigeria - Akomolafe, Comfort. O.; Aremu, Esther Temiwunmi (European Scientific Journal, ESJ, 2016)
This study examined the various alternative sources put in place in the public universities in Lagos State in financing the institutions. The study adopted descriptive research design. The population for the study was all the universities in Lagos State. The sample for this study comprised two public universities in Lagos state. A self-design questionnaire titled â€œAlternative sources of financing university inventoryâ€ (ASFUI) was used to gather information required from the budgetary section of the universities. The study revealed that the Federal University was able to employ more alternative sources of financing than the State University. However, none of the universities fully employed the available alternative sources. It also revealed that tuition was not an alternative source at undergraduate level in the Federal university. It was recommended that the universities should employ more alternative sources which are yet to be employed and the State University specifically should be involved in some income generated activities which are commercial in nature and not currently employed. Tuition should be introduced in the Federal Universities at undergraduate level with consideration to students from poor parents.